Engaging students through activity-based bingo games in immunology course: Determining students' perception and measuring its influence on academic performance - Mohan B. Sannathimmappa; Vinod Nambiar; Rajeev Aravindakshan (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: This study aims to evaluate how well bingo game-based activities serve as instructional tools to enhance student learning. MATERIALS AND METHODS: This prospective cross-sectional study was approved by the Institutional Ethics Committee. The study sample size was 145 MD3 year college of medicine students for the academic year 2023-2024. The evaluation instruments included the participants' exam grades, pre-test scores, post-test scores, and feedback. The study employed a mixed-methods approach combining quantitative and qualitative research methods to investigate how students perceived and interacted with the bingo game-based activity. The data were analyzed by Statistical Package for Social Sciences (SPSS) version 26. The association between exam and post-test scores was examined using the correlation coefficient and a straightforward regression analysis. The P value of less than 0.05 was deemed significant. RESULTS: The study comprised 145 students in total who completed all the tasks. The post-test scores (10.62 ± 1.73) showed a statistically significant improvement (P < 0.01) over the pre-test scores (6.3 ± 1.99). Most students (85-90%) thought that activities centered around bingo games were great tools for learning. Nine out of ten students said the game-based activity was engaging and enjoyable, that it inspired them to engage in group discussions, that it assisted them in identifying and concentrating on important topics, and that it improved their knowledge and helped them get ready for the final exam. Almost all the participants (>90%) suggested adding this exercise to the list of future topics. Overall, exam scores achieved by students for topics covered in the bingo-based activity (92.7 ± 4.96) were significantly higher (P < 0.01) than exam scores for topics not covered in the activity (83.75 ± 7.74). CONCLUSION: Bingo game is an effective learning strategy to promote students' learning in the immunology course. Furthermore, utilizing bingo games as a formative assessment technique can significantly improve students' learning and help them achieve higher scores on summative assessments.